2018
DOI: 10.1038/s41598-018-28000-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of climate changes in the Late Pleistocene and Holocene on niche conservatism of an arvicolid specialist

Abstract: Climate change is not only evident, but its implications on biodiversity are already patent. The scientific community has delved into the limitations and capabilities of species to face changes in climatic conditions through experimental studies and, primarily, Species Distribution Models (SDMs). Nevertheless, the widespread use of SDMs comes with some intrinsic assumptions, such as niche conservatism, which are not always true. Alternatively, the fossil record can provide additional data to solve the uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…While the fossil record indicates areas of known species presence in the past, caution should be taken when comparing it to ENMs developed from present‐day populations, especially considering projections to increasingly early time periods. The presence of fossils in some sites with low ENM suitability may reveal the past presence of populations with particular niche requirements not captured by the ENM; while high ENM suitability in areas with no fossils might indicate past occupied regions where no fossil trace of the species presence was preserved (Castellanos‐Frías et al, 2018; Hinojosa et al, 2016; Hoban et al, 2019). Further integration of evidence can be achieved where it is possible to measure the genetic diversity of ancient DNA from fossils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the fossil record indicates areas of known species presence in the past, caution should be taken when comparing it to ENMs developed from present‐day populations, especially considering projections to increasingly early time periods. The presence of fossils in some sites with low ENM suitability may reveal the past presence of populations with particular niche requirements not captured by the ENM; while high ENM suitability in areas with no fossils might indicate past occupied regions where no fossil trace of the species presence was preserved (Castellanos‐Frías et al, 2018; Hinojosa et al, 2016; Hoban et al, 2019). Further integration of evidence can be achieved where it is possible to measure the genetic diversity of ancient DNA from fossils.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ancient DNA in Cabrera vole have shown continuity of mitochondrial DNA haplotypes from the Mesolithic until about a thousand years ago, not found in the extant Iberian populations, supporting the hypothesis of a replacement of the fossil populations by current populations (Rodríguez‐Varela, 2016). In fact, Castellanos‐Frías et al (2018) suggested the possibility that the ecological niche of the Cabrera vole has changed with the climatic oscillations of the Quaternary, becoming broader during glacial times. Our results did not contradict this hypothesis, since the fossil record—namely in the MH—documents the species presence in regions outside the projected ecological niche calibrated with the current species distribution.…”
Section: Discussionmentioning
confidence: 99%
“…This has been interpreted as a potential source of error which causes mismatches between contemporaneous and fossil data derived niches (Castellanos-Frías et al, 2018; Guralnick and Pearman, 2009; McGuire and Davis, 2013; Rubidge et al, 2011). These mismatches are known as niche shifts, which are the variation in climatic preferences mainly derived from occurrence data (Broennimann et al, 2007; Castellanos-Frías et al, 2018; Davis et al, 2014; Guralnick and Pearman, 2009; McGuire and Davis, 2013; Worth et al, 2014). Considering the results obtained in this study, a shift in the niche of P. simplex would imply the existence of fast changes in allele frequencies during the last 4700 years or the ability to generate different phenotypes in response to novel environments or environmental changes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These should be inclusive/unbiased, which is a significant limitation in NUS production in marginal areas. Elith et al [117] noted that high collinearity is less of a problem for MLMs than statistical methods. However, we caution that this is only true if the presences' predictive accuracy is the study goal.…”
Section: Machine Learning-related Methodsmentioning
confidence: 99%